(untitled)
The bis(acetyl)-bridged complex [Pt(COMe)(2)(n)] (2) has been prepared from the platina-beta-di ketone [Pt(2)(COMe)(2)H)(2)(mu-Cl)(2)] (1) with hexamethyldisilazane. Reactions of complex 2 with the monodentate P and N donors PPh(3), pyrazole (Hpz), pyridine (py), 4-methylpyridine (4-Mepy), and benzylamine (BnNH(2)) resulted in the formation of the cis-diacetylplatinum(II) complexes cis-[Pt(COMe)(2)L(2)] (L = PPh(3), 3; Hpz, 5; py, 6a; 4-Mepy, 6b; BnNH(2), 7). Reactions with the bidentate N donors 2,2'-bipyridine (bpy), dimethylglyoxime (H(2)dmg), and pyridazine (pydz) resulted in formation of the complexes cis-[Pt(CoMe)(2)(L boolean AND L)] (L boolean AND L = bpy, 4; H(2)dmg, 8) and [Pt(2)(COMe)(4)(mu-pydz)(2)] (9), respectively. Furthermore, complex 2 has been found to react with acids such as HX (X = Cl, Br), generated in situ from Me(3)SiX/H(2)O, acetylacetone (Hacac), and hexafluoroacetylacetone (Hhfacac) to yield the known platina-beta-diketone 1, the new dinuclear bromo-bridged platina-beta-diketone [Pt(2)(COMe)(2)H)(2)(mu-Br)(2)] (10), and new mononuclear platina-beta-diketones [Pt(COMe)(2)H)(L boolean AND L)] (L boolean AND L = acac, 11; hfacac, 12). All complexes were characterized by means of microanalysis and IR and NMR spectroscopy. X-ray diffraction analyses were performed for complexes 10-12, showing a two-dimensional network built up by closed-shell Pt center dot center dot center dot Pt (d(8)-d(8)) interactions and bifurcated hydrogen bonds in crystals of complex 10 as well as infinite platinum chains built up by closed-shell Pt center dot center dot center dot Pt (d(8)-d(8)) interactions in crystals of complexes 11 and 12. Complexes 8, 11, and 12 have further been analyzed by UV/vis and luminescence spectroscopy in solution and in the solid state as well as time-resolved photo-emf measurements. Additionally, quantum chemical studies on the DFT level of theory revealed very strong O-H center dot center dot center dot O hydrogen bonds in the platina-beta-diketones 10-12 (25.6-27.9 kcal/mol)., author = Schwieger, Sebastian and Heinemann, Frank Wilhelm and Wagner, Christoph and Kluge, Ralph and Damm, Cornelia and Israel, Gunter and Steinborn, Dirk, doi = 10.1021/om9000499, faupublication = yes, journal = Organometallics, pages = 2485-2493, peerreviewed = Yes, title = A Bis(acetyl)-Bridged Platinum(II) Coordination Polymer as a Building Block for Diacetylplatinum(II) Complexes and Platina-beta-diketones, volume = 28, year = 2009